2013
DOI: 10.1128/microbiolspec.aid-0006-2012
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin E and Allergy: Antibodies in Immune Inflammation and Treatment

Abstract: The pathogenic role of immunoglobulin E (IgE) antibodies in triggering and maintaining allergic inflammation in response to allergens is due to the binding of multivalent allergens to allergen-specific IgEs on sensitized effector cells. These interactions trigger effector cell activation, resulting in release of potent inflammatory mediators, recruitment of inflammatory cells, antigen presentation, and production of allergen-specific antibody responses. Since its discovery in the 1960s, the central role of IgE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 153 publications
(154 reference statements)
0
1
0
Order By: Relevance
“…These interactions trigger effector cell activation, releasing potent inflammatory mediators, recruitment of inflammatory cells, antigen presentation, and production of allergen-specific antibody responses. 14 These events may cause responses at a local level, such as bronchoconstriction, vasodilation, and/or airway mucus secretion, and trigger the allergy-associated symptoms of nasal congestion, wheezing, sneezing, and cough, conjunctivitis, runny nose, dyspnoea, and chest tightness. 15 This study was conducted to examine the evidence for the effect of Th2 cytokine (IL-4) and total IgE on asthma severity and to investigate the possible ability of asthma control to reduce IL-4 levels and total IgE.…”
Section: Introductionmentioning
confidence: 99%
“…These interactions trigger effector cell activation, releasing potent inflammatory mediators, recruitment of inflammatory cells, antigen presentation, and production of allergen-specific antibody responses. 14 These events may cause responses at a local level, such as bronchoconstriction, vasodilation, and/or airway mucus secretion, and trigger the allergy-associated symptoms of nasal congestion, wheezing, sneezing, and cough, conjunctivitis, runny nose, dyspnoea, and chest tightness. 15 This study was conducted to examine the evidence for the effect of Th2 cytokine (IL-4) and total IgE on asthma severity and to investigate the possible ability of asthma control to reduce IL-4 levels and total IgE.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other Ig classes (IgA, IgE, or IgM) are being evaluated as anti-cancer therapeutic antibodies. For example, the therapeutic possibilities of an IgEbased immunotherapy [69,[73][74][75][76], including its safety [71,77], have been analyzed in renal carcinoma [67], breast cancer [68], ovarian cancer [78], and melanoma [79] models. All these analyses showed that the IgE was more effective than the corresponding IgG1 antibody.…”
Section: Introductionmentioning
confidence: 99%